(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2025)
This study examines the relationship between political instability and inflation in Libya from 1990 to 2021, employing an Autoregressive Distributed Lag (ARDL) model to analyse short- and long-term dynamics. The findings reveal a statistically significant positive relationship between political instability and inflation, with key mechanisms including supply chain disruptions, currency depreciation, and fiscal imbalances. The study underscores the importance of political stability for economic management and offers policy recommendations to mitigate inflationary pressures in Libya’s oil-dependent economy.